Manajemen Strategi Benchmarking Fluktuasi Suku Bunga (Analisis Sintesis dan Aantitesis Atas Rencana Pemerintah Mengganti SBI dengan T-Bills) - Manggala, Budi (Jurnal Manajemen, 2001)
The question now is why will the benchmarking of interest rate fluctuation be turned from SBIs into T-Bill?